Enzyme‐Instructed Intracellular Molecular Self‐Assembly to Boost Activity of Cisplatin against Drug‐Resistant Ovarian Cancer Cells. (14th September 2015) - Li, Jie; Kuang, Yi; Shi, Junfeng; Zhou, Jie; Medina, Jamie E.; Zhou, Rong; Yuan, Dan; Yang, Cuihong; Wang, Huaimin; Yang, Zhimou; Liu, Jianfeng; Dinulescu, Daniela M.; et al.
Abstract: Anticancer drug resistance demands innovative approaches that boost the activity of drugs against drug‐resistant cancers without increasing the systemic toxicity. Here we show the use of enzyme‐instructed self‐assembly (EISA) to generate intracellular supramolecular assemblies that drastically boost the activity of cisplatin against drug‐resistant ovarian cancer cells. We design and synthesize small peptide precursors as the substrates of carboxylesterase (CES). CES cleaves the ester bond pre‐installed on the precursors to form the peptides that self‐assemble in water to form nanofibers. At the optimal concentrations, the precursors themselves are innocuous to cells, but they double or triple the activity of cisplatin against the drug‐resistant ovarian cancer cells. This work illustrates a simple, yet fundamental, new way to introduce non‐cytotoxic components into combination therapies with cisplatin without increasing the systemic burden or side effects.